Q: What is 6d plus 1 equals 15 -1d?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

12

-6d = -42-6(7) = -42d = 7

They can be simplified to 10d

3d+7=6d+5 The first thing would be to subtract 3d from both sides. You will end up with 7=6d-3d+5. Then subtract 5 from both sides. Now you have 7-5=6d-3d. Now you have the numbers with like terms on either side of the equation. 7-5=2 and you can subtract 3d from 6d because both 6 & 3 have d as their variable. So 6d-3d=3d. Now the equation is 2=3d. Now you have to divide both sides by 3. (Since 3d is also expressed as 3 x d, we need to do the opposite of multiplication which is division, in order to get the variable d by itself) So now you have 2/3=d, or d is two thirds.

5d-4=4-d you have to bring the d to one side and the 4 to the other remember there is a 1 in front of the d so you'll get 6d-4=4 then you get 6d=8 then you divide and get d=4/3 or 1 and 1/3

Related questions

2(3d+7)=5+5d. 6d+14=5+5d 6d+9=5d 9=-1d d=-9 I think that's correct. If it is, ur welcome.

12

3c - 4d = 6d + 4c Subtract 4c from both sides: -c - 4d = 6d Add 4d to both sides: -c = 10d or c = - 10d

9d-19=6d+2 ... add 19 to both sides and subtract 6d from both sides... 9d-6d=2+19 3d=21 d=21/3 d=7

If -6d = 42 then 6d = -42. then divide by 6, d = -7

-6d = -42-6(7) = -42d = 7

That is an algebraic equation. If you are asking what the solution is for the above equation, it would be:d = 7

72-6d=6 subtract 72 from both sides -6d=66 divide by -6 d=-11

They can be simplified to 10d

6d = c Divide both sides by 6: d = c/d

Do you mean: 11d +1 = 5d+49? If so: 11d+1 = 5d+49 11d-5d = 49-1 6d = 48 d = 8

9d+3